Polyranger signal for synchronization restoration in discrete communication canal - S. s. Schaschkin (Известия высших учебных заведений России: Радиоэлектроника)
The structure of synchronization restoration signal (SRS) in discrete communication canals is considered. SRS is constructed on base of package with three frequency harmonics, allowing to change over a wide range an interval of ambiguous counting. Researches of a noise stability of such parcel and the recommendation about application of a parcel are given in channels of transfer of discrete messages.